2010
DOI: 10.1111/j.1365-2044.2009.06237.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mild induced hypothermia on the myocardium: a systematic review

Abstract: SummaryMild induced hypothermia improves neurological outcome and reduces mortality among initially comatose survivors of out-of-hospital cardiac arrest. Similar pathological processes occur in the heart and the brain, namely ischaemia followed by reperfusion injury. Animal data indicate that mild induced hypothermia results in improved myocardial salvage, reduced infarct size, reduced left ventricular remodelling and better long-term left ventricular function. Several small human studies suggest that infarct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…47 There is also evidence that TH may be beneficial to the heart in the postarrest period. Animal studies have shown improvement in myocardial function, myocardial salvage, and reduced infarct size in the setting of cardiac arrest or acute myocardial infarction with the use of TH.…”
Section: Circulatory Supportmentioning
confidence: 99%
“…47 There is also evidence that TH may be beneficial to the heart in the postarrest period. Animal studies have shown improvement in myocardial function, myocardial salvage, and reduced infarct size in the setting of cardiac arrest or acute myocardial infarction with the use of TH.…”
Section: Circulatory Supportmentioning
confidence: 99%
“…Early arterial hypotension is common and is associated with increased in-hospital mortality [1,3,4]. It is characterised by hypovolaemia [5], reversible myocardial stunning [4][5][6] and excessive vasodilation [7,8].…”
mentioning
confidence: 99%
“…We do not challenge the protective potency of hypothermia. However, we would like to draw attention to several reports describing cardiac disadvantages even under hypothermic conditions in humans (for review [2]). The Vijlbrief group itself has demonstrated impairment of cardiomyocytes by elevated troponin I levels in neonates after perinatal asphyxia under hypothermic conditions.…”
Section: Figmentioning
confidence: 99%